The Effect of Rainfall and Wind on Fishermen's Fish Catches in Bungsus Harbor, West Sumatra - Apriani, Cici; Elizal, Elizal; Tanjung, Afrizal (Journal of Coastal and Ocean Sciences, 2024)
The purpose of this study was to determine the effect of rainfall and wind on fish catches for fishermen at Bungus Ocean Port, West Sumatra. Rainfall and wind data were obtained from BMKG Teluk Bayur, Padang, while fish catch data were obtained from PPS Bungus staff, West Sumatra. The methods used in this research activity are the survey method and quantitative analysis. The results of this study showed that rainfall in the study area ranged from 0.01-15.4 mm, the average wind speed ranging from 1.0-1.6 m/s for the catch ranging from 334.983-560.145 kg. The results of the analysis between rainfall and wind on fish catches showed the correlation is not too intense because, based on the results of interviews, fishermen make voyage trips or fishing trips where fishing trips are carried out for more than one day, sometimes even more than one month, so additional data is needed for future research in the form of fishing trip data and data of ships departing per trip